Financiamento da pesquisa científica:avaliação da eficiência relativa partir de projetos de uma Instituição Federal de Ensino Superior - Francisco, Nara Antonio (2019)
This research aimed at analyzing the relative efficiency, by type of funding source, of the projects managed by the Science and Technology Support Foundation (Fatec) from the perspective of financing and scientific academic production. This is a quantitative research which was developed using Data Envelopment Analysis (DEA) method. The search for the documents that composed the corpus of the research took place on the Fatec Transparency Portal, on the Project Portal of the Federal University of Santa Maria (UFSM – Rio Grande do Sul, Brazil), as well as on the Lattes Platform, which also provides information on the academic and professional path of students and researchers. On the Web of Science database, the H index of the researchers could be verified. In order to measure efficiency, eight variables were considered in this research. Two of them are inputs: total financed amount and the value of permanent material; and six are outputs: H index, theses, dissertations, articles published nationally, articles published internationally, and patents. The sample consisted of 98 projects coordinated by researchers from the UFSM, which were financially managed by Fatec and completed between 2013 and 2017. Among the most efficient projects, the three types of financing could be found: public, private, and hybrid. The analysis has also shown that more than 60% of the projects have an efficiency score lower than 0.5, that is, very low. Therefore, regardless of their funding source, most projects are operating below capacity when compared to other projects that had similar investment.